2023
DOI: 10.1186/s12885-023-11548-0
|View full text |Cite
|
Sign up to set email alerts
|

First-line treatment with TKI plus brain radiotherapy versus TKI alone in EGFR-mutated non-small cell Lung cancer with brain metastases: a systematic review and meta-analysis

Yaowen Song,
Shuiyu Lin,
Jun Chen
et al.

Abstract: Background It remains uncertain whether first-line treatment with upfront brain radiotherapy (RT) in combined with epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) is superior to EGFR-TKIs alone for EGFR-mutated non-small cell lung cancer with newly diagnosed brain metastases (BMs). Therefore, we performed a meta-analysis to address this issue. Methods We searched PubMed, Embase, Cochrane Library, and Web of Science databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Additionally, in the subgroup of patients with the L858R mutation, the OS was significantly longer in the osimertinib plus upfront radiotherapy group compared to the osimertinib alone group (Zhai et al 2021 ). A meta-analysis of 24 studies that examined the effectiveness of combining upfront brain radiation therapy (RT) with first-/second-generation EGFR-TKIs compared to using only first-/second-generation EGFR-TKIs (Song et al 2023 ). The meta-analysis revealed that there was no significant discrepancy in the benefit of iPFS between the two groups, encompassing both asymptomatic and symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the subgroup of patients with the L858R mutation, the OS was significantly longer in the osimertinib plus upfront radiotherapy group compared to the osimertinib alone group (Zhai et al 2021 ). A meta-analysis of 24 studies that examined the effectiveness of combining upfront brain radiation therapy (RT) with first-/second-generation EGFR-TKIs compared to using only first-/second-generation EGFR-TKIs (Song et al 2023 ). The meta-analysis revealed that there was no significant discrepancy in the benefit of iPFS between the two groups, encompassing both asymptomatic and symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“… 37 Indeed, previous reports revealed that combination therapy with radiotherapy and EGFR TKI was associated with better outcomes than those achieved with TKI alone in EGFR mutation-positive NSCLC with brain metastases. 38 , 39 The biological rationale for differences in CNS metastasis development between 19del and L858R remains unclear owing to the limited insight into the genetic makeup of metastasis. The variation in resistance mutations and differences in co-occurring mutations may define the risk of CNS metastasis progression.…”
Section: Discussionmentioning
confidence: 99%